Dampak Konflik Anak Remaja di Kecamatan Medan Deli (Studi Kasus Dampak Sosial Remaja di Kelurahan Tanjung Mulia Hilir dan Kelurahan Tanjung Mulia) - Dalimunthe, Muhammad Rafly (Universitas Muhammadiyah Sumatera Utara, 2025)
Conflict among teenagers is a common social phenomenon, especially in densely populated urban environments. This study aims to analyze the social impact of adolescent conflict in Medan Deli District, focusing on Tanjung Mulia Hilir Village and Tanjung Mulia Village. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation of adolescents involved in the conflict, parents, community leaders, and local security forces. The results of the study indicate that adolescent conflict in this area is influenced by various factors, such as peer pressure, family economic conditions, and lack of parental supervision. The social impacts include an increase in brawls, crime, and decreased academic achievement among the adolescents involved. In addition, this conflict also causes social tension in the community, reduces the sense of security, and affects relationships between residents. This study suggests the need for intervention from various parties, including families, schools, and the government, to reduce adolescent conflict through a character education approach, positive activities for adolescents, and increased security in their residential areas. Thus, it is hoped that a more harmonious and conducive social environment can be created for the development of adolescents in Medan Deli District.